Relationship Between Mother's Knowledge About Acute Respiratory Infections Management And The Incidence Of Acute Respiratory Infections In Children In Wolo Village - Rauf, Raldi; Jasmin, Muh (PT. Nursing Genius Care, 2024)
Background Acute respiratory infections (ARI) are one of the causes of morbidity and mortality in children in poor and developing countries. Various factors trigger the high incidence of ARI, both the environment, congenital, and the knowledge of the public who still do not understand how to prevent ARI, especially mothers as child caregivers. Method This study describes the problem of ARI with a cross-sectional approach. The sample in this study was 50 mothers who had children aged 5-12 years. Determination of the sample using a purposive sampling technique. Research data were analyzed using the chi-square test. Results The study reveals an average maternal age of 31.8 years and a child age of 5.94 years. Most mothers completed high school or have a bachelor's degree. Maternal knowledge significantly impacts the incidence of Acute Respiratory Infections (ARIs) in children. Targeted educational interventions are needed to improve child health outcomes and reduce ARI burden. Conclusion The study reveals a significant link between maternal knowledge of Acute Respiratory Infections (ARI) management and the incidence of ARI in children in Wolo Village, with lower knowledge levels resulting in higher incidences.